Formation of a Trimeric Xpo1-Ran[GTP]-Ded1 Exportin Complex Modulates ATPase and Helicase Activities of Ded1. - Glenn Hauk; Gregory D Bowman (PLoS ONE, 2015)
The DEAD-box RNA helicase Ded1, which is essential in yeast and known as DDX3 in humans, shuttles between the nucleus and cytoplasm and takes part in several basic processes including RNA processing and translation. A key interacting partner of Ded1 is the exportin Xpo1, which together with the GTP-bound state of the small GTPase Ran, facilitates unidirectional transport of Ded1 out of the nucleus. Here we demonstrate that Xpo1 and Ran[GTP] together reduce the RNA-stimulated ATPase and helicase activities of Ded1. Binding and inhibition of Ded1 by Xpo1 depend on the affinity of the Ded1 nuclear export sequence (NES) for Xpo1 and the presence of Ran[GTP]. Association with Xpo1/Ran[GTP] reduces RNA-stimulated ATPase activity of Ded1 by increasing the apparent KM for the RNA substrate. Despite the increased KM, the Ded1:Xpo1:Ran[GTP] ternary complex retains the ability to bind single stranded RNA, suggesting that Xpo1/Ran[GTP] may modulate the substrate specificity of Ded1. These results demonstrate that, in addition to transport, exportins such as Xpo1 also have the capability to alter enzymatic activities of their cargo.